Meet the expert : the defining moment for data scientists in financial services with Daniel Lewington. (O'Reilly Media, Inc., 2021)
Sponsored by LSEG LABS The rapid acceleration in data-driven transformation that resulted from the COVID-19 pandemic is really just a glimpse of what's yet to come for financial services. In this edition of Meet the Expert, Daniel Lewington, director of innovation at the London Stock Exchange Group (LSEG), explores some of the biggest trends around data science in the financial services industry. Daniel and his team share findings from their in-depth research with global data practitioners on AI and machine learning strategies, use cases, data, tech, talent, and governance. Recorded on December 8, 2021. See the original event page for resources for further learning or watch recordings of other past events. O'Reilly Meet the Expert explores emerging business and technology topics and ideas through a series of one-hour interactive events. You'll engage in a live conversation with experts, sharing your questions and ideas while hearing their unique perspectives, insights, fears, and predictions.